Efektifitas Terapi Relaksasi Autogenik terhadap Tekanan Darah pada Lansia Hipertensi - Juwita ikram; Samsualam; Wa Ode Sri Asnaniar; Nur Ilah Padhila (Window of Nursing Journal, 2025)
Elderly is an age that experiences many changes in a life process, one of which is increased peripheral vascular resistance so that blood pressure increases or is commonly called hypertension. Autogenic relaxation therapy is expected to have an effect on reducing blood pressure in the elderly. This study aims to determine the Effect of Autogenic Relaxation Therapy on Blood Pressure in the Elderly with Hypertension in the Bontomarannu Health Center Work Area, Gowa Regency, South Sulawesi. This study used a Quasy Experiment design with the NonEquivalent Control Group Pretest ans Posttest method. And divided into two groups, namely the intervention group and the control group. The determination of the sample used the Krejcie and Morgan table according to the predetermined criteria with a sample size of 76 and divided into two groups, namely the intervention group of 38 people and the control group of 38 people. This study uses the Mann-Whitney Test statistical test with a significance level (ρ <0.05), from the results of the study that has been conducted it was found that Autogenic Relaxation Therapy has an effect on blood pressure p <0.00. The conclusion based on the results of the study, shows that there is an effect of Autogenic Relaxation Therapy on Blood Pressure in the Elderly with Hypertension in the Bontomarannu Gowa Health Center Work Area.